Pengaruh Jumlah Unit UMKM dan Tenaga Kerja UMKM terhadap Pertumbuhan Ekonomi di Kota Gorontalo - Isnawati Abas; Radia Hafid; Ardiansyah Ardiansyah; Melizubaida Mahmud; Agil Bahsoan (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study aims to determine the effect of the number of MSME units and the labor force on economic growth (GRDP) in Gorontalo City. The study method used is quantitative, with data analysis techniques employing classical assumption test and hypothesis testing, and analyzing the data using multiple linear regression analysis with the assistance of IBM SPSS 21 software. The data used in this study include secondary data obtained from the Statistics of Gorontalo City and the Department of Manpower, Cooperatives, and MSMEs of Gorontalo City. This study consists of a dependent variable, which is the economic growth (GRDP) of Gorontalo City, and independent variables, which are the number of MSME units and the labor force during the period of 2020-2024. The results indicate that simultaneously, the variables of the number of MSME units and the labor force affect economic growth (GRDP) in Gorontalo City significantly. The variable of the number of MSME units, when considered individually, has a positive and significant effect onn economic growth (GRDP) in Gorontalo City. Meanwhile, the labor force variable has a positive and significant effect economic growth (GRDP) in Gorontalo City.